Perceptions of Counsellors’ Intentions with High Versus Low Quality Counsellor Responses - Uhlemann, Max R.; Lee, Dong Yul; Martin, Jack (Canadian Journal of Counselling and Psychotherapy, 1993)
The study examined the relationship between high and low quality counsellor responses in seven response modes and client perceptions of counsellor intentions. Sixty-four high school students viewed 14 videotaped interview-vignettes that presented high and low quality counsellor responses of reflection of feeling, questions, paraphrasing, interpretation, self-disclosure, confrontation, and advice. The students responded to the Intention List to indicate their perceptions of the intentions behind the counsellor responses in each vignette. Of the seven counsellor response modes, six revealed somewhat different client perceptions of counsellor intentions under conditions of high versus low quality responses. Overall, however, only 10 to 56 relevant comparisons demonstrated such differences. Implications of the results are discussed.